Improved sintering performance of β-SiAlON–Si3N4 and its osteogenic differentiation ability by adding β-SiAlON. (April 2022) - Mu, Jinghua; Zhang, Liguo; Zhang, Can; Xu, Enxia; Wang, Lulu; Liu, Xinhong; Chang, Guanglei; Sun, Xu; Ma, Chengliang; Yuan, Huiyu; Zhao, Fei; Gao, Jinxing
To improve the sintering performance of silicon nitride bioceramics, we explored the effect of β-SiAlON's Z-value on the physical, chemical, and biological properties of β-SiAlON–Si3 N4 composites. Results showed that the phase product was β-Si3 N4 . As the Z-value increased, the X-ray diffraction peaks gradually shifted to a smaller angle, the material grains were more tightly packed, and the bulk density and compressive strength increased, reaching the highest values (2.71 g/cm 3 and 1157 MPa, respectively) at Z = 4. Soaking and ion-release experiments show that in an aqueous environment, a small amount of Al and Si ions were released, and no obvious decomposition occurred on the surface of the material. The biological performance showed that the growth of cultured cells in each group was in good condition, there was no obvious difference in morphology and adhesion, and the materials had good biological performance. An increase in the Z-value promotes the formation of mineralized nodules and osteogenic differentiation of MC3T3-E1 cells, which may be because the release of Si can promote osteogenic differentiation. Therefore, the addition of β-SiAlON could improve the sintering performance of β-Si3 N4 without degrading its biological properties. The prepared β-SiAlON–Si3 N4 composite ceramic is a latent bioceramic material.